(untitled) (Journal of Pedagogical Inventions and Practices, 2024)
Academic vocabulary is crucial for students’ success in school and beyond, yet many learners struggle with mastering these essential words. This article explores effective strategies for teaching academic vocabulary to students of all ages. It begins with an overview of the importance of academic words and the challenges faced by students in acquiring them. The article then delves into various teaching strategies, including direct instruction, contextual learning, active engagement, word consciousness, teaching word parts, and repetition and review. Additionally, it highlights the role of technology in enhancing vocabulary instruction and the importance of assessment and feedback in monitoring students’ progress. By implementing these strategies, educators can help students develop a strong academic vocabulary, which is a key component of academic success.